Reconsidering the Cellular Response to Orthodontic Tooth Movement. From Mechanical to Biochemical Perspectives - Gaitán-Salvatella, Iñigo (2026)
Orthodontic tooth movements are a complex process that involves mechanical forces applied to teeth, leading to changes in the periodontal ligament, alveolar bone, dental pulp, and neovasculature tissue. The mechanosensitive influence of the electrical signals through ion channels plays a significant role in understanding the cell signaling pathways and cell differentiation to increase and promote bone remodeling and regeneration. The mechanism of cell signaling in response to bioelectric potential due to mechanical loading, including mechanosensing, transduction, and cellular responses, facilitated the tooth movement in response to mechanical forces. Moreover, the neurovascular unit plays a crucial role during orthodontic tooth movement, which involves the coordinated activity of osteoclasts and osteoblasts to reshape the alveolar bone. The review aims to present the biological processes that underpin the cellular response, explicitly focusing on the role of signal transduction during the biological tissue response of the orthodontic tooth movement to deepen our understanding of this mechanism.